Molecular, morphological and pathogenic diversity of Sclerotinia sclerotiorum isolates from common bean (Phaseolus vulgaris) fields in Argentina - Aban, Carla Luciana (2018)
White mould, caused by Sclerotinia sclerotiorum, is one of the most threatening fungal diseases occurring across major bean production regions worldwide. In Argentina, under favourable weather conditions, up to 100% seed yield losses occur on susceptible common bean cultivars. The aim of this study was to characterize the diversity of S. sclerotiorum isolates from six dry bean fields in the main production area of Argentina by means of molecular, morphological (mycelium colour, number and pattern of sclerotia distribution) and pathogenic approaches. Among 116 isolates analysed, high genotypic and morphological variability was observed. A total of 52 mycelial compatibility groups (MCGs) and 59 URPs (universal rice primers) molecular haplotypes were found. All the MCGs were location specific, while only 12% of the URP haplotypes were shared among locations. The molecular analysis of variance revealed a significant differentiation among populations, with higher genetic variability within the populations analysed than among them. The aggressiveness of the isolates towards bean seedlings was assessed in the greenhouse. Most of the isolates were highly aggressive, while no variation among locations was observed. The information generated in the present study provides, for the first time, information on the variability of S. sclerotiorum associated with white mould in the main common bean production area in Argentina. In addition, the findings suggest the occurrence of both clonal and sexual reproduction in the populations analysed. This work contributes to the development of sustainable manageme